Inkjet Printed Spiral Stretchable Electronics Using Reactive Ink Chemistries. Issue 51 (14th June 2016) - Mamidanna, Avinash; Song, Zeming; Lv, Cheng; Lefky, Christopher S.; Jiang, Hanqing; Hildreth, Owen
ABSTRACT: Fabrication methods and performance characteristics of spiral stretchable interconnects fabricated using drop-on-demand printing of silver reactive inks are discussed. This work details ink optimization, device fabrication, and device characterization while demonstrating the potential applications for reactive inks and new design strategies in stretchable electronics. Devices were printed with an ethanol stabilized silver diamine reactive ink and cycled to 160 % over 100 cycles with less than 10% increase in electrical resistance. Maximum deformation before failure was measured at 180% elongation. A novel method for fabrication of a stretchable electronics device has been studied and verified.